Diagnostic accuracy of dried blood spot samples for hepatitis B diagnosis: a systematic review and meta-analysis - Songhe Wang; Xitong Yao; Xinyu Zhang; Jiaoqiang Chen; Pin Han; Wei Bai (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Introduction Hepatitis B virus (HBV) infection remains a major global public health problem. Dried blood spot (DBS) sampling is simple to collect, stable during transport, and easy to store, and may therefore provide an alternative sampling strategy for decentralized HBV testing. Content PubMed, Web of Science, MEDLINE, and Cochrane were searched for English-language studies published up to August 19, 2025. Eligible studies used DBS as the index test and venous blood, serum, or plasma testing as the reference standard. Summary Forty-four studies were included, yielding 61 datasets: 36 for HBsAg, 11 for anti-HBc, and 14 for HBV DNA. Based on the bivariate random-effects model, the pooled sensitivity and specificity of DBS-based HBsAg testing were 0.943 (95 % CI, 0.916–0.962) and 0.988 (95 % CI, 0.980–0.993), respectively, with a pooled DOR of 1,995.07 (95 % CI, 834.68–4,768.66). The pooled sensitivity and specificity were 0.836 (95 % CI, 0.737–0.902) and 0.973 (95 % CI, 0.937–0.989) for DBS-based anti-HBc testing, and 0.869 (95 % CI, 0.787–0.922) and 0.963 (95 % CI, 0.932–0.980) for DBS-based HBV DNA testing, respectively. Subgroup analyses showed that specificity remained relatively stable across most subgroups. Leave-one-out sensitivity analyses showed no directional change in the overall results after omitting individual studies. Outlook DBS-based HBsAg testing showed high diagnostic accuracy, supporting its use in community screening, primary care, and resource-limited settings. DBS-based anti-HBc and HBV DNA testing also showed high specificity, but their sensitivity was relatively lower. Further standardization of sample volume, filter paper type, elution procedures, storage conditions, and positivity thresholds is needed.